Variation in the Attitudes of Medical Oncologists Toward Research Biopsies in Patients With Metastatic Breast Cancer. (3rd August 2015) - Seah, Davinia S.; Scott, Sarah; Guo, Hao; Najita, Julie; Lederman, Ruth; Frank, Elizabeth; Sohl, Jessica; Stadler, Zsofia; Silverman, Stuart; Peppercorn, Jeffrey; Winer, Eric; Come, Steve; et al.
Abstract: Background: Tissue from research biopsies provides access to insights into tumor biology. We aimed to determine medical oncologists' (MOs') attitudes toward research biopsies in patients with metastatic breast cancer (MBC). Materials and Methods: A total of 309 breast MOs from National Cancer Institute (NCI)-designated cancer centers were invited to complete a self-administered survey about their attitudes toward approaching patients for research purpose-only biopsies (RPOBs), performed as a standalone procedure, or additional biopsies, performed with a clinically indicated biopsy. The MOs were asked to predict what proportion of their MBC patients would consider undergoing research biopsies. Results: Of the 309 MOs, 221 (72%) responded. Of these 221 MOs, 30 were ineligible, leaving 191 eligible responders. Nearly all the MOs reported they were comfortable approaching patients regarding research biopsies of blood or skin. One fifth of MOs were uncomfortable approaching patients for RPOBs of the breast. One half of MOs were uncomfortable approaching patients for RPOBs of the liver. A significant variation was found in the perceptions by MOs of their patients' willingness to undergo research biopsies. The factors associated with increased comfort in approaching patients for research biopsies included fewer years in practice, caring for patients who had undergone recent research biopsies, and the predicted willingness of patients to consent to biopsies. The risk of a biopsy and biopsy-related pain were the most common reasons for reluctance to refer patients for research biopsies. Conclusion: Significant variation exists, even at NCI centers, in the comfort level of MOs in approaching MBC patients for research biopsies. MOs' attitudes toward research biopsies might be a modifiable factor in increasing tissue collection for research. Implications for Practice: Tissue-based research is critical in advancing our understanding of cancer biology, and obtaining tissue from a research biopsy provides an essential resource. This study demonstrates the variability of oncologists' attitudes toward research biopsies and elicits factors associated with increased comfort levels with approaching patients for research biopsies. Biopsy risk and biopsy-related pain were commonly cited reasons not to refer patients for research biopsies. If the risk of a research biopsy is deemed sufficiently low enough to be acceptable, oncologists' attitudes might be a potential target for education and change, which may assist in increasing the availability of tissue for cancer research. Abstract : Medical oncologists' (MOs') attitudes toward research biopsies in patients with metastatic breast cancer were evaluated. Nearly all MOs reported they were comfortable approaching patients regarding research biopsies of blood or skin but many were less comfortable approaching patients for research purpose-only biopsies of the breast and liver. Significant variation exists, even at National Cancer Institute cancer centers, in the comfort level of MOs in approaching MBC patients for research biopsies.